2018
DOI: 10.1111/tid.13009
|View full text |Cite
|
Sign up to set email alerts
|

Risk of hepatitis B reactivation in hepatitis B surface antigen seronegative and core antibody seropositive kidney transplant recipients

Abstract: Background: Previous contact with Hepatitis B virus (HBV) is common in patients undergoing hemodialysis. Literature has shown conflicting results on the risk of HBV reactivation in kidney transplant (KT) recipients with serologic evidence of past HBV infection. Methods: We reviewed 631 consecutive KT recipients and selected 70 patients simultaneously HBsAg negative and anti-HBc positive before KT, regardless of hepatitis B surface antibody (anti-HBs) status. Demographic characteristics, coinfection with other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…To date, several previous studies have reported the risk of HBV reactivation among HBsAg‐negative, anti‐HBc‐positive KT recipients. In these studies, the reported reactivation risk was low, ranging from 0.9% to 6.4% 17‐21 . Among studies that focused on the reactivation risk in recipients who received rituximab, one study found a very low risk of HBV reactivation (2.2%, one patient) among 48 patients who received rituximab, 22 whereas another study found a relatively high risk of HBV reactivation (10.2%, 5 patients) among 49 patients who used rituximab 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several previous studies have reported the risk of HBV reactivation among HBsAg‐negative, anti‐HBc‐positive KT recipients. In these studies, the reported reactivation risk was low, ranging from 0.9% to 6.4% 17‐21 . Among studies that focused on the reactivation risk in recipients who received rituximab, one study found a very low risk of HBV reactivation (2.2%, one patient) among 48 patients who received rituximab, 22 whereas another study found a relatively high risk of HBV reactivation (10.2%, 5 patients) among 49 patients who used rituximab 15 .…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, the reported reactivation risk was low, ranging from 0.9% to 6.4%. [17][18][19][20][21] Among studies that focused on the reactivation risk in recipients who received rituximab, one study found a very low risk of HBV reactivation (2.2%, one patient) among 48 patients who received rituximab, 22 whereas another study found a relatively high risk of HBV reactivation (10.2%, 5 patients) among 49 patients who used rituximab. 15 To the best of our knowledge, this study is the largest to date to report the risk of HBV reactivation including patients who used rituximab (n = 66), which was not high (3%, 3 patients).…”
Section: Discussionmentioning
confidence: 99%
“…Active HBV replicates had been detected in extrahepatic reservoirs such as lymph nodes, spleen, pancreas, and even brain, thus providing an extrahepatic source for a potential HBV reactivation 4,14 . However, the main source for HBV reactivation is the covalently linked cccDNA of HBV in the infected liver, which is removed at LT, thus explaining the difference in the HBV reactivation rate of 2.9% in a recently published study in 70 HBsAg‐negative/anti‐HBc‐positive kidney transplant recipients 15 . The median follow‐up time was comparable (12.0 vs 12.5 years), and no NA prophylaxis was administered in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…These donors can also be offered to HBsAb+ recipients, who will not require antiviral prophylaxis. Post‐transplant HBV reactivation in HBsAg‐negative and HBcAb‐positive patients is rare but possible, so evaluation with HBV serologies, HBV viral load and liver enzymes before transplantation and monitoring serologic HBV markers after transplantation is suggested 111 . Patients who are not vaccinated against HBV or are HBV naïve can also receive HBcAb+ kidneys since the risk of transmission is low, but antiviral prophylaxis such as lamivudine for 1‐year post‐transplant is suggested in this setting.…”
Section: Hepatitis B (Hbv) In Eskdmentioning
confidence: 99%